The Emerging WDM EPON - Radivojević, Mirjana; Matavulj, Petar (Springer International Publishing : Imprint: Springer, 2017)
This book proposes dynamic wavelength and bandwidth allocation (DWBA), a hybrid of time-division multiplexing (TDM) and wavelength-division multiplexing (WDM), which offers a solution for service providers faced with multiservice networks. It discusses different models, architectures and implementations and evaluates their performance.